On-board real time vision based sensor implementation on UAV for features detection technique of low altitude mapping / Nor Hashim Mohd Arshad … [et al.] - Mohd Arshad, Nor Hashim; Misnan, Mohamad Farid; Ahmad Shauri, Ruhizan Liza; Abdul Razak, Noorfadzli; M. Thamrin, Norashikin (Research Innovation Business Unit, 2014)
It is a difficult task for a remotely operated aerial vehicle to manoeuvre and navigate effectively over an area to perform some tasks. Putting some form of intelligence into the control system of the aerial vehicle and combining it with a good detection system will be helpful to automate the manoeuvre and navigation. The idea is to implement simple algorithm to process digitized analog images which are captured using simple analog video cameras. This could be used to detect features over a simulated physical surrounding of a small portion of a paddy field. The processed data is used to assist in performing effective navigation for the unmanned aerial vehicle over the paddy field. Simplified hardware and algorithm are essential to produce a minimum load required by the unmanned aerial vehicle.